Impacts of Landscape Change on Water Resources - Jha, Manoj K.; Jha, Manoj K. (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Changes in land use and land cover can have many drivers, including population growth, urbanization, agriculture, demand for food, evolution of socio-economic structure, policy regulations, and climate variability. The impacts of these changes on water resources range from changes in water availability (due to changes in losses of water to evapotranspiration and recharge) to degradation of water quality (increased erosion, salinity, chemical loadings, and pathogens). The impacts are manifested through complex hydro-bio-geo-climate characteristics, which underscore the need for integrated scientific approaches to understand the impacts of landscape change on water resources. Several techniques, such as field studies, long-term monitoring, remote sensing technologies, and advanced modeling studies, have contributed to better understanding the modes and mechanisms by which landscape changes impact water resources. Such research studies can help unlock the complex interconnected influences of landscape on water resources in terms of quantity and quality at multiple spatial and temporal scales. In this Special Issue, we published a set of eight peer-reviewed articles elaborating on some of the specific topics of landscape changes and associated impacts on water resources.
English
Keywords: History of engineering & technology; LID practices; watershed scale; impervious area; peak flow; surface runoff; shallow subsurface runoff and infiltration; evapotranspiration; stream temperature; SWAT; Marys River watershed; soil temperature; solar energy; watershed model; landscape scale; VELMA; bank erosion; landscape metrics; diversity; Sajó River; UAV; spatial configuration units; best management practices (BMPs); spatial optimization; hydrologic response units (HRUs); hydrologically connected fields; slope positions; watershed process simulation; DMMF; landscape configuration; landscape ecology; hydrology; scaling-up conservation agriculture; drip irrigation; groundwater potential; sustainable intensification; Ethiopia; flood analysis; hydrologic modeling; hydrodynamic modeling; HEC-RAS; flood zone delineation; landscape change; water resources analysis; water modeling; impact assessment